Territorio y nacionalidad en Iberoamérica tras las Independencias. El principio constitucional uti possidetis juris: razones y estrategias para contar su historia - Lorente, Marta (Jahrbuch für Geschichte Lateinamerikas, 2018)
This article tackles the constitutional nature of the principle of uti possidetis in the light of its impact on the development of Ibero-American constitutional history. Even though this principle may be considered as one of the most peculiar elements of such an academic field, the fact that uti possidetis has been almost exclusively studied by lawyers and international legal scholars has led to a systematic exclusion of this subject matter from the conventional Ibero-American historiography. Despite the lack of accounts on it, the principle of uti possidetis has played a major role in international conferences and treaties, not to mention its relevance when demarcating Ibero-American national communities, histories, and geographies.